2010
DOI: 10.1007/s00365-010-9117-4
|View full text |Cite
|
Sign up to set email alerts
|

Restricted Isometry Property of Matrices with Independent Columns and Neighborly Polytopes by Random Sampling

Abstract: This paper considers compressed sensing matrices and neighborliness of a centrally symmetric convex polytope generated by vectors ±X 1 , . . . , ±X N ∈ R n , (N ≥ n). We introduce a class of random sampling matrices and show that they satisfy a restricted isometry property (RIP) with overwhelming probability. In particular, we prove that matrices with i.i.d. centered and variance 1 entries that satisfy uniformly a sub-exponential tail inequality possess this property RIP with overwhelming probability. We show … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
134
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(134 citation statements)
references
References 28 publications
0
134
0
Order By: Relevance
“…The result is optimal, up to the factor log log 3m, as shown in [2]. As for Theorem 7, assuming unconditionality of the distributions of the rows, we can remove this factor.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…The result is optimal, up to the factor log log 3m, as shown in [2]. As for Theorem 7, assuming unconditionality of the distributions of the rows, we can remove this factor.…”
Section: Resultsmentioning
confidence: 88%
“…The articles [1], [2] and [3] considered random matrices with independent columns, and investigated high dimensional geometric properties of the convex hull of the columns and the RIP for various models of matrices, including the log-concave Ensemble build with independent isotropic log-concave columns. It was shown that various properties of random vectors can be efficiently studied via operator norms and the parameter Γ n,m recalled below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, approximate message passing algorithms (AMP) for compressed sensing reconstruction [8], [4] can be recast in the form (1) for suitable choices of the matrix A and functions f . Generalizations of this algorithm were developed by several groups [17], [15], [14] Here, we will use the term AMP for the generalized recursion (1). We also notice that the universality of compressed sensing phase transitions can be conjectured from the results of the non-rigorous replica method [13], [16].…”
Section: Resultsmentioning
confidence: 97%
“…We say that the sequence is (C, d)-regular (or, for short, regular) polynomial sequence if (1) For each N , the entries (A ij (N )) 1≤i<j≤N are independent centered random variables. Further they are subgaussian with common scale factor C/N .…”
Section: A Universalitymentioning
confidence: 99%